1998
DOI: 10.1177/088307389801301203
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Bihemispheric Structural and Functional Defects in Sturge-Weber Syndrome

Abstract: Abnormal cerebral venous drainage is associated with hypoxia and glucose deprivation, which can account for progressive neurologic deterioration in Sturge-Weber syndrome. Although developmental delay is common in Sturge-Weber syndrome, bihemispheric calcification is uncommon. Computed tomography (CT) and magnetic resonance imaging (MRI) were used to study the neuroanatomy, while single photon emission computed tomography (SPECT) was used concurrently to evaluate perfusion and glucose metabolism using 99mTc hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…14 Bilateral cerebral involvement is uncommon. 15-17 Experimental blood flow studies using the 133 Xe single-photon emission computed tomography (SPECT) technique have shown decreased flow in the involved cerebral region, and one blood flow study showed that a seizure can cause a significant reduction of flow in remote, uninvolved cerebral regions, in effect a vascular steal phenomenon. 1 …”
Section: Advances and Questions In The Definition Neurological Symptmentioning
confidence: 99%
“…14 Bilateral cerebral involvement is uncommon. 15-17 Experimental blood flow studies using the 133 Xe single-photon emission computed tomography (SPECT) technique have shown decreased flow in the involved cerebral region, and one blood flow study showed that a seizure can cause a significant reduction of flow in remote, uninvolved cerebral regions, in effect a vascular steal phenomenon. 1 …”
Section: Advances and Questions In The Definition Neurological Symptmentioning
confidence: 99%
“…Nevertheless, it is unclear whether abnormal blood perfusion in the affected WM directly contributes to the clinical features of SWS. Previous functional neuroimaging, such as positron emission tomography (PET) and single photon emission computed tomography (SPECT) studies have found that blood flow deficit in the affected cortical regions was common in SWS, probably contributing to neurologic impairment [79]. Recent dynamic contrast enhanced MR perfusion weighted imaging (PWI) studies have also shown similar results [10–12].…”
mentioning
confidence: 91%
“…The first cerebral lesion diagnosed in this patient was a small left temporal hemorrhage. Stroke-like episodes [7], deep cerebral venous occlusion [8] and hemiplegic migraine [9] may occur in SWS. Although the most common presentation of arteriovenous malformations of the brain is cerebral hemorrhage [10], intracranial bleeding is not a "major problem" in SWS [1].…”
Section: Discussionmentioning
confidence: 99%